Applications of Transcutaneous Electrical Nerve Stimulation in Dentistry - Katch, Eric M. (1986)
TENS is extremely useful in some dental procedures, such as TMJ syndrome and tooth extraction; however, its use is not practical in all situations. The dentist must remember that TENS is an adjunctive form of treatment. It is not a panacea for all types of pain, nor should it be used as a last resort. When applied correctly and with care, TENS is useful in the management of pain in the head and face.